THE EFFECTIVENESS OF COLLABORATIVE STRATEGIC READING ON STUDENTS’ READING COMPREHENSION - Yusi Anita (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2018)
The objective of this research was to find whether collaborative strategic reading was effective to improve students’ reading comprehension on SMPN 1 Gondanglegi Malang. The participants are students from 8D and 8C Class. The first group was 8D as the experimental group, and the control group was 8C. The data mainly came from statistical results, including the questionnaire responses. The scores of both groups were analyzed by using independent sample t-test. The result of independent sample t-test showed that the probability (p) was less than level of significant which is 0.05, it was .000. It means there is a significant difference between students who are taught by using Collaborative Strategic Reading than they who are not. The mean score obtained by experimental group was higher than the mean score obtained by the control group (74.58 > 62.66). It shows that there was a positive effect after applying Collaborative Strategic Reading in the experimental group. Thus, it can be concluded that Collaborative Strategic Reading is effective to improve students’ reading comprehension. Keywords: Collaborative Strategic Reading, Reading Comprehension, Effectiveness